Space Baby - "Dalton, Annie" (Egmont Books: London, 2002)
Life is hard for Cameron since Dad left and when he finds a Space Baby, things become even more difficult. His brother's gang are after the baby and it's up to Cameron, his sister and Grandma to protect the alien and pull the family back together
Keywords: Fantasy fiction